Elevated cellular PpIX potentiates sonodynamic therapy in a mouse glioma stem cell-bearing glioma model by downregulating the Akt/NF-κB/MDR1 pathway - Kenji Shono (Nature Portfolio, 2021)
Abstract Glioblastoma (GBM) has high mortality rates because of extreme therapeutic resistance. During surgical resection for GBM, 5-aminolevulinic acid (5-ALA)-induced protoporphyrin IX (PpIX) fluorescence is conventionally applied to distinguish GBM. However, surgical intervention is insufficient for high invasive GBM. Sonodynamic therapy (SDT) combined with low-intensity ultrasonication (US) and PpIX, as a sonosensitizer, is an emerging and promising approach, although its efficacy is limited. Based on our previous study that down-regulation of multidrug resistant protein (MDR1) in GBM augmented the anti-tumor effects of chemotherapy, we hypothesized that elevation of cellular PpIX levels by down-regulation of MDR1 enhances anti-tumor effects by SDT. In high invasive progeny cells from mouse glioma stem cells (GSCs) and a GSC-bearing mouse glioma model, we assessed the anti-tumor effects of SDT with a COX-2 inhibitor, celecoxib. Down-regulation of MDR1 by celecoxib increased cellular PpIX levels, as well as valspodar, an MDR1 inhibitor, and augmented anti-tumor effects of SDT. MDR1 down-regulation via the Akt/NF-κB pathway by celecoxib was confirmed, using an NF-κB inhibitor, CAPÉ. Thus, elevation of cellar PpIX by down-regulation of MDR1 via the Akt/NF-κB pathway may be crucial to potentiate the efficacy of SDT in a site-directed manner and provide a promising new therapeutic strategy for GBM.